1996
DOI: 10.1007/bf01955183
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model to estimate the risk of serious bacterial infections in febrile infants

Abstract: CRP, duration of fever, the "standardized clinical impression score", a history of diarrhoea and focal signs of infection were the independent, most powerful predictors of SBI in febrile infants, identified by logistic regression analysis. Although the predictive model is not validated for direct clinical use, it illustrates the clinical potential of the used technique. This technique offers the advantage of assess the probability of SBI in every individual infant. This probability will form the best basis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 23 publications
2
62
0
1
Order By: Relevance
“…In one study that used blinded assessments by infectious disease experts to determine the presence of true bacteremia, catheter-drawn cultures had a VOL. 19,2006 UPDATED REVIEW OF BLOOD CULTURE CONTAMINATION 793 sensitivity of 89%, compared to 78% for peripheral cultures, with a positive predictive value of 63% for catheter-drawn cultures versus 73% for percutaneous cultures (34). The results of that study were similar to those of other studies, leading many to suggest that if cultures are obtained from a catheter, at least one set should be drawn percutaneously (13,20,38,74,76,92).…”
Section: Source Of Cultures (Catheter Drawn Versus Percutaneous)supporting
confidence: 71%
See 2 more Smart Citations
“…In one study that used blinded assessments by infectious disease experts to determine the presence of true bacteremia, catheter-drawn cultures had a VOL. 19,2006 UPDATED REVIEW OF BLOOD CULTURE CONTAMINATION 793 sensitivity of 89%, compared to 78% for peripheral cultures, with a positive predictive value of 63% for catheter-drawn cultures versus 73% for percutaneous cultures (34). The results of that study were similar to those of other studies, leading many to suggest that if cultures are obtained from a catheter, at least one set should be drawn percutaneously (13,20,38,74,76,92).…”
Section: Source Of Cultures (Catheter Drawn Versus Percutaneous)supporting
confidence: 71%
“…Although controversial, some experts recommend that the culture site be prepped with 70% isopropyl or ethyl alcohol and allowed to air dry and that a VOL. 19,2006 UPDATED REVIEW OF BLOOD CULTURE CONTAMINATION 795…”
Section: Skin Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[18][19][20][21][22][23] Variables of the selected CPRs were matched with the alarm signs in the GPC-dataset. In case alarm signs were not entirely identical to the original CPR variables, best proxy variables were used.…”
Section: Selection Of Cprs and Translation To The Primary Out-of-hourmentioning
confidence: 99%
“…Clinical prediction rules may, alongside guidelines, help physicians to identify children at low risk of disease. [19][20][21][22][23][24][25] The only clinical prediction rule developed for primary care specifically showed a promising high sensitivity and low negative likelihood ratio at derivation; 6 however, it lacked generalisability on external validation in other low-prevalence populations. 17 In addition, another study has shown that other clinical prediction rules developed for hospital emergency care were of limited use in the primary outof-hours care setting as well.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%